A assistência ao estudante da Residência Universitária da UFPB - Barbosa, Roseane de Almeida (2009)
This study aims to analyze the student assistance within the university residences. It is known that with the reality of students, interpersonal relationships, the dreams and perspectives, or see in their area of living your day to day. The study was conducted through field research, from students to veterans and rookies in the period May-June 2007 in two university residences located in the neighborhood of the Center and the Campus I of UFPB in João Pessoa. To develop this research was necessary to define a sample of approximately 10%, twenty-four students from a universe of three hundred. Used as a tool to collect the form with open and closed questions, and analysis of data in the tables, the graphics in addition to desk research and literature search. The study suggests that assistance to students has been maintained through efforts punctual, not always sufficient, the units of community and student affairs of each institution. It is essential that the education policy includes assistance to students who really is unable to remain in college. The student assistance is important for achieving a higher level of training qualified. Therefore, this study aims to contribute not only new knowledge but also to broaden the debate on the issue of student assistance, as public policy, those who really need support for their academic and professional development.